Medicinal plants of Sabah (East Malaysia) for women's health - Tanduba, Carynn (Philippine Journal of Science, 2025)
Women from local ethnic groups in Sabah employ medicinal plants from their immediate surroundings for their health. These plants could be of value for developing drugs or over-thecounter herbal remedies. Data in this review were compiled from library search, ScienceDirect, Web of Science, PubMed, and Google Scholar, as well as from the 15th century to 2025; other sources were excluded. For the online search, the following combination of keywords was selected: “medicinal plants,” “Sabah,” and “women”. Each result was reviewed, and papers lacking information about plant species (scientific and local names), specific ailments treated, and ethnic groups of Sabah were excluded. Papers published in non-peer-reviewed journals were also eliminated. Analysis of the data reveals that 67 species of medicinal plants are utilized in treating women’s health conditions in Sabah. These plants are mainly monocots and core angiosperms, principally employed by Bornean ethnic groups (Dusuns) for postpartum care. Among these, eight plants have not been fully identified, whereas one is unknown. Nine plants stand out as especially promising for further research. In summary, collective evidence supports the conclusion that the ethnopharmacopoeia of Sabah comprises a unique range of medicinal plants, some of which have the potential to be processed into medicines or health supplements for women's wellness locally and internationally.